DAMPAK GLOBALISASI TERHADAP PEREKONOMIAN GLOBAL - Muammil Sun'an (Trunojoyo University of Madura, 2010)
Globalization has generated a process of capitalism of nation-state towards a very new phase. Since 1992, world has related each other in one social system through commercial and financial activities integrated in an international market. But since 1960 until now, the statement is getting more acceleration, economic activities on the world has begun a way to a new global economy. The implementation of economic activities started from the transaction of goods, services, and factors of production, and then followed by more economic integration among countries.Globalization of economy causes a dominant role of non-state economic actors with great international economic activities, called multinational corporation or (transnational corporation, TNCs). As a result, economic activities on the world are dominated by the businessmen who have internationalized their activities through expansion, exporting so many products and sales to many countries where they (the businessmen/companies) don't have loyalties to a nation-state particularly and do their investment and run their businessmen in